2005
DOI: 10.1177/003335490512000212
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lead Poisoning among Cuban Refugee Children

Abstract: Risk factors for lead poisoning among immigrant children may differ from those among U.S.-born children. Screening of immigrant children who may have been exposed in their country of origin and education of immigrant parents about lead exposure hazards associated with activities such as car repair should be considered in the design of lead poisoning prevention and control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…These were risks from electrical appliances, child safety, knowledge and use of emergency procedures, fire safety, risks from poisoning, hygiene and food safety and the importance of being and feeling safe at home. Studies in America have identified similar issues when working with refugees (Dempsey & Orr, 2006; Trepka et al. , 2005; Upvall & Bost, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…These were risks from electrical appliances, child safety, knowledge and use of emergency procedures, fire safety, risks from poisoning, hygiene and food safety and the importance of being and feeling safe at home. Studies in America have identified similar issues when working with refugees (Dempsey & Orr, 2006; Trepka et al. , 2005; Upvall & Bost, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Household hobbies involving lead have been associated with childhood lead poisoning in other Caribbean countries, 27,28 although sources of lead exposure can differ by island and country. 29 Bernard and McGeehin (2003) reported education (High School graduate or not) of the reference adult was associated with being in the 5-10 μg/dL BLL group (OR: 1.5 [95% CI: 1.0, 2.2]) and the 10-20 μg/dL BLL group (OR: 2.2 [95% CI: 1.3, 3.8]) among children sampled in the Third NHANES, 1988–1994. 23 Another study reported on the inverse relationship between child BLL and parental education attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Lead-acid car batteries were used in camp households to generate power for electronic items, and have been associated with lead poisoning in the developing world 21 and even among certain immigrant children inside the United States. 22 Such batteries were easily accessible to toddlers engaging in exploratory and mouthing behaviors in the camps. Car battery exposure is unlikely to continue after resettlement, but the identified traditional remedies, cosmetics, and spices could be easily brought overseas.…”
Section: Discussionmentioning
confidence: 99%